English Club Mini : Private Program For Training English Speaking Kids - Riski Angreini; Khairunnisah; Rahmat Huda; Shoufi Nisma Dewi; Devinna Riskiana Aritonang (CV. Alfa Pustaka, 2025)
This English language service or training focuses on those aged 8-12 years, through interesting activities that improve their English speaking skills. The objectives of carrying out this training are: 1) To train and improve children's communication in using English, 2) To enrich children's vocabulary in English which they will be able to use later after they are at a higher school level, 3) To motivate children to dare to speak English in front of the class or public. The learning technique used to train children's English is Show and Tell and also using Flipper Books and pictures. Using qualitative methods and emphasizing memorization and recitation tasks will increase participation and accountability among children. This training lasted for three days, emphasizing enriching language skills and fostering a positive attitude towards learning. After carrying out this training, it is of course hoped that it will improve children's English language skills, making them much more confident and have skills that they can apply in the future.